Perancangan Desain Karakter Pada Komik Web Sejarah Lokal “Gedangan 1904” - Yuningsih, Agustina Putri; Daniar, Aninditya; Nisa, Diana Aqidatun (Innovative: Journal Of Social Science Research, 2024)
Indonesia has a long history as a country that was colonized for almost 350 years. This makes Indonesia rich in historical heritage, both national and local in every region. The importance of building awareness of historical continuity, especially for the younger generation, is necessary to preserve historical sites and heritage. One of the efforts made is to introduce local history to the younger generation through a webcomic titled "Gedangan 1904," which tells the story of the colonial events in Sidoarjo, East Java. This comic combines two timelines, namely the year 2024 and 1904, to make the historical message more relevant and engaging for the target audience. In the process of its creation, character design becomes an important element to strengthen the storyline. This article discusses the process of designing the main character in the comic "Gedangan 1904," with the aim of preserving local history through a creative approach.